Moderation in the light of Islamic Sharia - Waqar, Dil Aqa; Hashimy, Sayid Ahmad (Journal of Islamic Sciences, 2023)
The main objective of this study is to demonstrate the moderative characteristics and features of Islam among the religions, as this moderation is shining in all the worships in Islam, such as praying only takes few minutes, fasting is only once in a year, Zakat is only obligatory on those who are rich, and pilgrimage is only once in the whole life upon those who can afford it. Islam does not prevent us from enjoying the pleasures of the world, such as eating, drinking, marriage, and the like of what is permitted in our daily lives. Therefore, taking legitimate adornment and benefiting from good things is required in our Shariah. We are blameless of those who distorted the image of true and moderate Islam, so it is our duty to invite people to this divine, moderate approach. Moderation is among the characteristics of this nation, so as long as this nation is a moderate nation, it must represent moderation in all that is related to their family (personal), social, political, and moral lives, otherwise we would contradict God’s designation (the moderate) for this nation and religion, and this is never permissible. As for the methodology for this study is concerned, they are descriptive and analytical research methods in which they rely on authentic books and research studies and presents practical examples. The result of the study demonstrates that Islam is the true religion of having moderation in all its aspects and that Muslims are on the path of moderation towards all people. Also, the moderation in Islam is not only by sayings without practical implementation, rather it is a theory that is implemented in all aspects of the Islamic Shariah.